2018
DOI: 10.3174/ajnr.a5597
|View full text |Cite
|
Sign up to set email alerts
|

3D Deep Learning Angiography (3D-DLA) from C-arm Conebeam CT

Abstract: Deep learning angiography accurately recreated the vascular anatomy of the 3D rotational angiography reconstructions without a mask. Deep learning angiography reduced misregistration artifacts induced by intersweep motion, and it reduced radiation exposure required to obtain clinically useful 3D rotational angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The qualitative and quantitative analysis demonstrated reliable visualization of the anterior and posterior circulation and excellent agreement with the current criterion standard 3D DSA. The results are in accordance with the recent literature: Montoya et al [15] were the first to describe the feasibility of an AI-based method to reconstruct DSA-like 3D volumes from a cerebral rotational angiography without using a mask run. The authors observed in a quantitative analysis a nearly 100% correspondence between their AIbased and the conventional method and stated that an AIbased 3D-angiography approach accurately recreates vascular anatomy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The qualitative and quantitative analysis demonstrated reliable visualization of the anterior and posterior circulation and excellent agreement with the current criterion standard 3D DSA. The results are in accordance with the recent literature: Montoya et al [15] were the first to describe the feasibility of an AI-based method to reconstruct DSA-like 3D volumes from a cerebral rotational angiography without using a mask run. The authors observed in a quantitative analysis a nearly 100% correspondence between their AIbased and the conventional method and stated that an AIbased 3D-angiography approach accurately recreates vascular anatomy.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Montoya et al described a novel alternative method based on artificial intelligence (AI) to generate DSA-like 3D volumes of cerebral vasculature [15]. The authors demonstrated the general feasibility of the method and concluded in the quantitative analysis that it accurately recreates vascular anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Four ML algorithms were selected for model building since these have shown good performance in clinical healthcare classification studies. 20,30,31,35,36 The models include the standard statistical logistic regression (LR), support vector machine (SVM, with linear [L-SVM] and Gaussian [G-SVM] kernels), k-nearest neighbor (k-NN), and neural network (NN). An illustration of the concept of each algorithm is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We note that it typically takes a couple of years for biomedical graduate students to reach the level of expertise required to conduct reliable CFD simulations of cerebral aneurysm hemodynamics. While rapid progress in machine learning algorithms is posed to automate image segmentation (136,137) and dramatically reduce modeling time and cost, knowledge of flow physics and cardiovascular mechanics will likely remain necessary for patient-specific hemodynamic analysis. Since it is impractical to train medical practitioners in advanced CFD modeling and implausible that each medical center will keep on staff a modeling expert, the remaining alternative is to use cloud-based computing to conduct flow analysis at dedicated centers.…”
Section: Conducting Modeling Studies In a Clinical Settingmentioning
confidence: 99%
“…Cartesian grids allowed these authors to avoid meshing luminal surfaces and could be easily refined to improve the resolution in smaller vessels. Adopting deep learning algorithms for image segmentation will allow further reduction of the modeling time and automated elimination of image artifacts, as evidenced by innovative studies applying neural networks to CTA data and 3D angiograms of cerebral arteries (136,137,140).…”
Section: Conducting Modeling Studies In a Clinical Settingmentioning
confidence: 99%